DETERMINING MATERIALS REQUIREMENT PLANNING OF REMANUFACTURED DUMP TRUCK AT X COMPANY - YOTANTI - NIM 13413051 , TISA
PT X is a heavy equipment manufacturing company with has remanufacturing business sector. One of the products which is remanufactured by PT X is dump truck engine. Besides engine, PT X also provides remanufacturing in the form of subcomponents such as turbo charger and fuel pump. The engines and subcomponents received by PT X (called core) come from different regions such as Belgium, America, Australia and South Africa. The remanufacturing product produced by PT X is composed of new and old parts that have been manufactured. Some spare parts which conditions do not conform for machining should be replaced with new parts. However, since new spare parts suppliers are abroad, the lead time is very long (3 months). As a result, number of ordered parts must be determined long before PT X sees the real condition of the used product. This causes the company to make an assessment of the number of replacement parts. So far, the company uses average historical replacement and is equipped with expert judgment in determining the quantity order. However, companies often experience deficiencies that can reach 7 out of 10 orders. This has an impact on emergency orders with the price of goods rising by 800%. Therefore, the company needs to think about how to determine the best order quantity. In this research used Material Requirement Planning (MRP) approach which is commonly found in manufacturing system for determining quantity order. However, in order to overcome the problem of uncertain conditions of parts received by PT X then it is modified with the application of replacement ratio in MRP. The replacement ratio is calculated based on the stratified number of replacement per machine's origin region. In addition, the best lot size is also determined. Based on this research, the best material planning method is obtained by calculating the average replacement ratio per region. The best order size determination method is done by Silver-Meal method. The total cost savings of the three average spare parts of Rp 8,861,314 were reduced by 55% of the total current cost.